Genetic testing and surveillance guidelines in hereditary pheochromocytoma and paraganglioma. (15th January 2019) - Muth, A.; Crona, J.; Gimm, O.; Elmgren, A.; Filipsson, K.; Stenmark Askmalm, M.; Sandstedt, J.; Tengvar, M.; Tham, E.
Abstract: Pheochromocytoma and paraganglioma (PPGL) are rare tumours and at least 30% are part of hereditary syndromes. Approximately 20% of hereditary PPGL are caused by pathogenic germ line variants in genes of the succinate dehydrogenase complex (SDHx), TMEM127 or MAX . Herein we present guidelines regarding genetic testing of family members and their surveillance based on a thorough literature review. All cases of PPGL are recommended genetic testing for germ line variants regardless of patient and family characteristics. At minimum, FH, NF1, RET, SDHB, SDHD and VHL should be tested. In addition, testing of MEN1, SDHA, SDHAF2, SDHC, TMEM127 and MAX is recommended. Healthy first‐degree relatives (and second‐degree relatives in the case of SDHD and SDHAF2 which are maternally imprinted) should be offered carrier testing. Carriers of pathogenic variants should be offered surveillance with annual biochemical measurements of methoxy‐catecholamines and bi‐annual rapid whole‐body magnetic resonance imaging and clinical examination. Surveillance should start 5 years before the earliest age of onset in the family and thus only children eligible for surveillance should be offered pre‐symptomatic genetic testing. The surveillance of children younger than 15 years needs to be individually designed. Our guidelines will provide a framework for patient management with the possibility to follow outcome via national registries and/or follow‐up studies. Together with improved insights into the disease, this may enable optimisation of the surveillance scheme in order to minimise both anxiety and medical complications while ensuring early disease detection.